Have space suit--will travel - Heinlein, Robert A. (Robert Anson) 1907- (New York Ace Books, 1958)
A high school senior wins a space suit in a soap jingle contest, takes a last walk wearing "Oscar" before cashing him in for college tuition, and suddenly finds himself on a space odyssey.